Enhancing Learning through Constructive Alignment in Vocational Schools in Cameroon - Yaro Loveline (Researchparks Publishing, 2021)
Through out the years, teaching and learning approaches have evolved in so many ways and in different educational context and settings. In Cameroon for instance, teaching and learning approaches have experienced paradigm shifts from the objective approach, to the New Pedagogic approach and now to the Competency based approach. The importance of learning outcomes is central to teaching and learning in schools especially in vocational training where the focus has moved to knowledge acquisition to knowledge construction through problem solving competences. This implies that teaching and learning should undoubtedly be more learner centered. Thus, Pedagogy needs to align with constructive learning theories with great consideration on the guiding principles of constructive alignment that takes into account the different purposes and settings in which learning takes place. Vocational education plays a very vital role in the socioeconomic growth of a country. Constructive alignment approach is aimed to improve students learning outcome in vocational schools through it application by deliberately aligning the intended learning outcome to the teaching learning activities and the assessment. Based upon constructive learning theory(constructivism) aligned curriculum can be achieved by focusing on what the students does. the use of constructive alignment approach in vocational schools should align the learning outcome to the three key elements of constructive alignment which are the learning outcomes, the teaching learning activities and the assessment strategies, this plays a key role in producing a skilled workforce and create the local workforce needed by the industry and the country. Using the quasi-experiment research design, the study advocates for a more constructive aligned instruction in technical colleges in Cameroon.